Respostas bioquímicas e hematológicas de jundiás (Rhamdia quelen) pré-alimentados com vitamina C e expostos a atrazina - Gomes, Jeane de Lima Costa (2016)
This study was conducted at the laboratory of Biology and Adaptive Aquatic Toxicology, as well as at the Pisciculture Laboratory, both from the Federal University of Santa Maria (UFSM). The overall objective was to evaluate the antioxidant effects of vitamin C on biochemical and hematological parameters of jundiá Rhamdia quelen. The study was divided in two experiments (phase), and the results of the first experiment served as the basis for the second period. The first step consisted in preparing food supplemented with vitamin C in 3 different concentrations: (1) 0 (2) and 500 (3) 1000 mg / kg. During supplementation were collected 10 fish per diet on days 0, 7, 14, 21 and 28, for the purpose of performing a concentration curve to ascertain the minimum amount of supplementation it to obtain the protective effect of vitamin C. In each collection, blood, liver and gill samples were collected for subsequent biochemical and hematological analysis. Our results showed that the activity of catalase (CAT) in the liver, increased, only in group 1, with no significant changes in the other groups. The levels of lipid peroxidation in liver and gills were reduced in groups 2 and 3 compared to group 1. The activity of glutathione peroxidase (GPx) in liver increased both in group 2 and in group 3 compared to group 1. The protein carbonyl content in gills was higher in group 1 when compared to others groups. Regarding the activity of glutathione Stransferase enzymes (GST) and superoxide dismutase (SOD) and the level of non-protein thiols (NPSH), there was no significant difference between groups. The total erythrocyte count (RBC), hemoglobin (Hb) and hematocrit (HCT) increased in all groups. There were no significant differences in relation to the mean cell volume (MCV) and mean cell hemoglobin (MCH) values. From the results obtained it was observed that the amount of 500 or 1000 mg/kg vitamin C were sufficient to improve the antioxidant ability to Rhamdia quelen and it was established that 28 days of feeding would be a minimum to obtain desired results. Through these assumptions began the second phase of the study, where animals were fed for 30 days with feed containing 1000 mg/kg of vitamin C. The animals were divided into the following groups: (1) control Vitamin C 0 mg/kg (2) control vitamin C 1000 mg/kg, (3) exposure to atrazine vitamin C 0 mg/kg, (4) exposure to atrazine vitamin C 1000 mg/kg. After the feeding period the animals were subjected to exposure atrazine at a concentration of 10μg/L, for a period of 96 hours. The purpose of this step was to determine whether this amount of vitamin C would be sufficient for fish protection against stress caused by exposure to the herbicide. At this stage we choose to perform analysis only in the liver, since the gill showed few significant changes in the first phase of the experiment. The results of this phase showed that in all groups there was no significant difference in lipid peroxidation. However, there was a decrease in protein carbonyl content in group 4 when compared to the other groups. NPSH levels increased only in the groups supplemented with 1000 mg/kg vitamin C (groups 2 and 4). There was no significant difference in the GST activity among the groups. The GPx activity increased significantly in group 4 as compared to the other groups. The CAT activity decreased both in groups 3 and 4. Thus, we conclude that vitamin C improved liver protection when the animals were exposed to atrazine. Therefore, a diet supplemented with adequate amounts of vitamin C, can provide both good nutrition for the fish as well as a protection against stress factors.